Intersectionality as an analytical tool for approaching psychosocial interventions in social psychology - Correa Duque, María Cristina (2026)
Intersectionality is a tool that allows analyzing the relationship in which different axes of social categorization such as gender, sexuality, ethnicity, class, functional diversity, age or level of education, among others, are intertwined in a complex manner in the processes of domination. Likewise, it is evident that in the field of psychology intersectionality is a novel concept and it is expected to progressively transform the most traditional psychological practices and perspectives. This review seeks to recognize the concept of intersectionality assumed by the field of social psychology, from the psychosocial intervention in Colombia, whose contribution contributes to the comprehensive and situated understanding of the realities of oppression and privilege, which social groups in the country experience on a daily basis. The methodological design proposed is one with a qualitative approach, and corresponds to a literature review, using the web tool Tree of Science (ToS), which uses the structure of the citation network to identify relevant literature. The findings found in the literature review indicate that Social Psychology has assumed intersectionality and has considered it as an approach that allows guiding the analysis and reflections on social categorization, stereotypes, stigmatization, inequality and social justice. Intersectionality allows social and community psychologists to understand and take action, in a comprehensive manner, on the different structural problems experienced in Colombia such as: violence resulting from the armed conflict, femicides and gender violence, migration, police and institutional abuses and discrimination.